KONSEP SEKULARISASI DALAM PEMIKIRAN NURCHOLISH MADJID - Budi Prayetno (Sulesana, 2017)
The purpose of this research is to understand the secularization issue proposed by Nurcholish Madjid which is derived from the idea of renewing Islamic thinking. To achieve this objective, this research uses literature review method with the intention to trace how the idea of Nurcholish Madjid renewed. The approach used is by using the historical approach. The results of this research is the secularization initiated by Nurcholish Madjid in the 1970s is a response to the issue of modernization that developed especially among Indonesian Muslims. Nurcholish sees that secularization is necessary because Muslims are no longer able to distinguish between sacred and profane issues. Secularization is intended for Muslims to worldly things that are supposed to be worldly and to disengage the tendency for the sacred. One background of the idea of secularization is to respond to the idea of forming an Islamic state which according to Nurcholish Madjid is a form of failure of Muslims in responding to the problem of modernization.